Case report: Transmural migration of a gossypiboma with secondary cystolithiasis and urethral obstruction - Lancaster, Meghan L.; Schmiedt, Chad W. (Frontiers in Veterinary Science, 2024)
This report describes a case of transmural migration of a gossypiboma from the peritoneum into the urinary bladder in a 4-year-old, female spayed, mixed breed dog. The dog presented on an emergency basis for complete urethral obstruction with radiographic evidence of urocystolithiasis. An exploratory laparotomy was performed and a 4-5 cm mass was identified which was confluent with the apex of the urinary bladder. The mass and bladder were exteriorized and isolated, and an apical, partial cystectomy was performed to remove the mass and gain access to the uroliths within the lumen of the bladder. A 4x4 surgical sponge was identified within the trigone of the bladder with multiple incorporated uroliths; another sponge was found within the mass itself. This case demonstrates an atypical cause of urethral obstruction and serves as the first reported case of transmural migration of a gossypiboma into the urinary bladder of a dog. It also illustrates the importance of establishing routine operating procedures including gauze counts and the use of radiopaque labeled surgical gauze.